2021
DOI: 10.1002/smi.3028
|View full text |Cite
|
Sign up to set email alerts
|

Personality antecedents of challenge and threat appraisal

Abstract: It has been suggested in personality and emotion theories that traits can influence emotional states and behaviour through interpretive processes such as cognitive appraisals. The present study investigated the relationships between Big Five personality dimensions and the cognitive appraisal processes associated with challenge and threat states in a large sample of municipal firefighters. The study assessed the Big Five traits and cognitive appraisal tendencies using a new measure of challengethreat appraisal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Additionally, the findings of the mediation analyses align with the cognitive appraisal model (Smith and Ellsworth 1987). According to the cognitive appraisal theory, both psychological traits and situational factors influence whether individuals appraise a testing situation as a challenge or threat (Wiese-Bjornstal et al 1998;Li 2009;Tomaka and Magoc 2021). Spatial anxiety, similarly to cognitive test anxiety, may be related to lower selfconfidence and lower test performance by an effect on emotional/physiological arousal during cognitive tasks, task-irrelevant thoughts, and attention (Bargh and Cohen 1978;Seibert and Ellis 1991;Cassady and Johnson 2002;Sullivan 2002;Roos et al 2021).…”
Section: Discussionsupporting
confidence: 58%
“…Additionally, the findings of the mediation analyses align with the cognitive appraisal model (Smith and Ellsworth 1987). According to the cognitive appraisal theory, both psychological traits and situational factors influence whether individuals appraise a testing situation as a challenge or threat (Wiese-Bjornstal et al 1998;Li 2009;Tomaka and Magoc 2021). Spatial anxiety, similarly to cognitive test anxiety, may be related to lower selfconfidence and lower test performance by an effect on emotional/physiological arousal during cognitive tasks, task-irrelevant thoughts, and attention (Bargh and Cohen 1978;Seibert and Ellis 1991;Cassady and Johnson 2002;Sullivan 2002;Roos et al 2021).…”
Section: Discussionsupporting
confidence: 58%
“…For example, a study by Liu et al (2021) found that individuals with high extraversion and neuroticism perceive greater COVID‐19 threat and thus experience increased stress compared with the pre‐pandemic period. Another study by Tomaka and Magoc (2021) showed that personality traits shape individuals' cognitive appraisals of different stressful situations. Accordingly, they found that individuals high on extraversion, conscientiousness, and openness to change tend to develop a challenge appraisal in response to many stressful situations, while those high in agreeableness and neuroticism are likely to make fewer challenge appraisals but more threat appraisals of various stressful events.…”
Section: Discussionmentioning
confidence: 99%
“…While extensive research has explored the broad trait of curiosity across different contexts (Silvia & Kashdan, 2009), less attention has been given to the experience of taskspecific curiosity. Few studies have investigated how curiosity about a particular task can enhance stress coping mechanisms, such as viewing stress as a challenge rather than a threat (Tomaka & Magoc, 2021). Furthermore, little is known about how task curiosity influences cardiac reactivity, an indicator of motivational intensity and task engagement (Behnke et al, 2021;Richter et al, 2016).…”
Section: Running Head: Curiosity Enhances Performancementioning
confidence: 99%
“…Research has shown that more open individuals evaluate stress differently. They generally perceive situations as challenging rather than threatening, RUNNING HEAD: CURIOSITY ENHANCES PERFORMANCE especially during public speaking (Penley & Tomaka, 2002;Tomaka & Magoc, 2021;Schneider et al, 2012). This primarily results from a more favorable evaluation of one's abilities rather than underestimating situational demands.…”
Section: Openness To Experiencementioning
confidence: 99%